Flesh or fish? - Piezonka, Henny (Documenta Praehistorica, 2013)
Graves and their human remains not only shed light on burial customs and social structures of past populations, but also constitute an excellent archive of prehistoric environmental and living conditions. Especially 13C/15N isotope analysis has recently opened up promising perspectives for reconstructing changes in diet and their social, cultural and economic background. Such investigations have been started on material from the Stone and Early Metal Age hunter-gatherer cemetery of Sakhtysh IIa in the Upper Volga region of Central Russia, where 15 burials associated with the early Lyalovo culture (5th mill. calBC) and 57 graves of the Volosovo culture (4th 3rd mill. calBC) have been excavated. In this paper, we present new AMS dates and isotopic data from four burials, two from the earlier and two from the later group. The results are discussed against the background of existing dates from Sakhtysh IIa burials and compared with information from other burial sites of Northern Europe.
Keywords: arheološke najdbe; grobovi; naselja; prazgodovina; Rusija